Етнокультурна специфiка метафоричної об’єктивацiї концепту ВРОДА (на матерiалi англійської та української/росiйської мов) - Довганюк, Е.В.; Dovhaniuk, E.V. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2014)
Робота присвячена виявленню та аналізу етнокультурної специфіки способів об’єктивації естетичного концепту ВРОДА в мовних свідомостях носіїв англійської та української/російської мов на основі концептуально-метафоричного аналізу із залученням лінгвокогнітивного та лінгвокультурологічного підходів. Работа посвящена определению и анализу этнокультурной специфики способов объективации эстетического концепта КРАСОТА в языковом сознании носителей английского и украинского/русского языков на основе концептуально-метафорического анализа с привлечением лингвокогнитивного и лингвокультурологического подходов. The research focuses on revealing and analyzing the ethnocultural peculiarities of the ways the aesthetic concept BEAUTY is represented in English and Ukrainian/Russian on the basis of a conceptual-metaphorical analysis within the framework of cognitive linguistics and linguoculturology.
Ethno-cultural peculiarities of the metaphorical objectivization of the concept BEAUTY in English and Ukrainian/Russian
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics; естетичний концепт; етнокультурна специфіка; когнітивна лінгвістика; лінгвокультура; метафора; aesthetic concept; сognitive linguistics; ethocultural peculiarities; linguoculture; metaphor